POTENTIALITY OF SOME TRADITIONAL MANGO CULTIVARS OF WEST BENGAL - SHUVADEEP HALDER (The Bioscan, 2020)
The predominant mango growing districts in West Bengal are Maldah, Murshidabad, Nadia and North 24- Parganas. Among them Murshidabad alone is known to have about 125 cultivars, but unfortunately very few of them viz. Himsagar, Langra, Fazli, Gopalbhog, Lakham bhog, Rani pasand, Amrapali etc, are commercially exploited. Keeping this in view ten cultivars were studied for their physical, chemical properties and yield for their commercial exploitation in mango industry and also for breeding work. Considering fruit quality cultivar champa and Panja Pasand are having more TSS, sugar and vit c content than Himsagar. In case of yield cultivar Champa gives a moderate yield but Panja Pasand gives higher yield than Himsagar. Though the Cultivar Kohitur is a poor yielder but higher weight, pulp percentage and good fruit quality carries a great historical value of West Bengal. The West Bengal Government has already claimed GI tag for it and in Kolkata market they are selling at Rs.1500-2000/ piece. Other cultivars Rani Pasand and Jahanara are good in fruit quality as well as giving a handsome yield. So, the cultivars like- Champa, Panja Pasand, Rani Pasand and Jahanara have great potentiality for commercial exploitation as well as table variety.